Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia - Kosterin, Oleg E. (Zootaxa, 2018)
Lestes nigriceps Fraser, 1924 was described from a male (later the lectotype) and two non-conspecific females collected in 1922 at Pusa, Bihar State, India, and has never been reported since. In June 2018 a population of L. nigriceps was unexpectedly found in eastern Cambodia, Mondulkiri Province. The Cambodian males, their variation and, for the first time, the true female of L. nigriceps is described.